Dual-crosslinked thiol-ene/sol gel hybrid electrospun nanowires: preparation and characterization - OKTAY, BURCU; KAHRAMAN, MEMET VEZİR (SPRINGER, 2015)
In this report, we describe the preparation and characterization of cross-linked electrospun membranes by using a reactive electrospinning. A novel methacrylate functional poly(vinyl alcohol) (M-PVA) was synthesized by reacting PVA and isocyanatoethyl methacrylate (2-ICEMA). The crosslinked membranes were achieved in a simple process at a single step using thiol-ene reaction between M-PVA and 3-mercaptopropyl trimethoxysilane (MPTMS) during the electrospinning process. In order to improve theirs the stability, the crosslinked membranes were also thermally treated. The morphology was characterized by scanning electron microscopy (SEM). The structure of M-PVA was characterized by attenuated total reflectance FT-IR. Morphological investigations show that the resulting membranes have nanowires morphology. The thermal analysis of the electrospun membranes was also investigated. Thermal stability of the membranes was improved with the incorporation of the sol gel precursor. The described method provides novel route for organic-inorganic hybrid membranes.
Keywords: Nanostructures; Polymers; Chemical synthesis; Electron microscopy; HYDROGELS